Vibration analysis on palm oil methyl ester biodiesel as a fuel with the additional of butanol - J. M., Zikri; M. S. M., Sani; Erdiwansyah, .; Ahmad Fitri, Yusop; I., Izzudin; Syazwana, Sapee (IOP Publishing, 2019)
Along with the development of alternative fuel to replace the usage of petroleum-derivatives, the vibration in the diesel engine has become one of the main focus by researchers recently. The biodiesel has been investigated numerously since the application does not need any modification of the engine and with the different fuel properties, the biodiesel can enhance or deteriorates the engine. Hence, this study will be carried out to investigate the effect adding butanol in two different biodiesel blends by using vibration analysis. The vibration level will be determined in velocity term in RMS by using uniaxial accelerometer. The results indicated that the B10Bu10 blend shows a better reduction in vibration level with the decrement more than 30% for both speed in 25% load while in the 50% load, the decrement was observed to be 13.46% for 1800 RPM and 22.9% for the 2100 RPM. Finally, it can be conclude that the usage of biodiesel with the additional of butanol can improve the vibration level in the diesel engine, however, with an additional volume of biodiesel in the blend tends to increase the vibration level in certain condition.